2020
DOI: 10.1039/c9sc05538j
|View full text |Cite
|
Sign up to set email alerts
|

Harpagide, a natural product, promotes synaptic vesicle release as measured by nanoelectrode amperometry

Abstract: Nanoelectrode amperometry was used to monitor DA release inside single DAergic synapses, and demonstrated that harpagide effectively enhances synaptic DA release by reducing intracellular ROS generation and inhibiting α-Syn phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 59 publications
0
22
0
1
Order By: Relevance
“…Because overactivated microglia cells are known to cause inflammatory response which is a key player in PD, and harpagide is suggested to possess anti‐inflammatory effects to reduce the overproduction of neuronal peroxides in agreement with our observations. [ 23 ] Therefore, we want to further investigate the neuroprotective effect of hapagide under vivo‐like (DA neurons‐microglia co‐culture) environment. The coimmunostain by TH (DA neuronal marker, green), CD11b/c (microglial marker, especially for the activated microglia, red) and Hoechst (cell nucleus marker) in Figure S2 indicated the successful culture of DAergic neurons and microglia in co‐cultured system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because overactivated microglia cells are known to cause inflammatory response which is a key player in PD, and harpagide is suggested to possess anti‐inflammatory effects to reduce the overproduction of neuronal peroxides in agreement with our observations. [ 23 ] Therefore, we want to further investigate the neuroprotective effect of hapagide under vivo‐like (DA neurons‐microglia co‐culture) environment. The coimmunostain by TH (DA neuronal marker, green), CD11b/c (microglial marker, especially for the activated microglia, red) and Hoechst (cell nucleus marker) in Figure S2 indicated the successful culture of DAergic neurons and microglia in co‐cultured system.…”
Section: Resultsmentioning
confidence: 99%
“…[ 18‐21 ] It has been shown that harpagide can facilitate axon regeneration of injured DAergic neurons, and maintain neurotransmitter dopamine (DA) release by reducing ROS level in injured neurons. [ 22‐23 ] However, in real pathological process, the initial factor of PD neuronal injury is nerve inflammation caused by microglial activation and the consequent neuron loss. It remains unknown whether harpagide protects neurons from inflammation‐mediated injury by inhibiting microglial activation.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Furthermore, the postsynaptic potential was successfully monitored with a glass nanopipette electrode, which again indicated that SCG-SMC synapses built in a microchip functioned effectively. This unique approach offers a platform to understand the true nature of neuronal exocytosis and the effect of drugs or chemicals, for example, harpagide, on it (Tang et al, 2020 ).…”
Section: Single-cell Amperometry For Monitoring Neurotransmitter Relementioning
confidence: 99%
“…Tang et al used carbon fiber nanoelectrodes (CFNEs) to monitor exocytotic events occurring inside single dopaminergic synapses. 4 They showed that the natural product, harpagide, managed to enhance synaptic DA release and restore DA release at normal levels from injured neurons in a Parkinson’s disease model by inhibiting ROS-induced phosphorylation and aggregation of α-synuclein.…”
Section: Electrochemical Analysis Of Single Cells and Organellesmentioning
confidence: 99%